ANALISA RASIO KEUANGAN SEBAGAI ALAT PENILAI KINERJA KEUANGAN PADA KOPERASI SENTOSA SAMARINDA SEBERANG - ., Isnawati (EKONOMIA, 2013)
Analysis ratio statements as tool evaluation of the financial statements to koperasi sentosa samarinda seberang. The data to examine who to make analysis there is report profit-lose year 2010, 2011, and 2012 with balance period 2010, 2011 and 2012.Method to break problem who the use there is with to use ratio liquiditas,(current ratio and cash ratio),ratio leverage (total debt to total capital asset and total debt to equity ratio), and ratio activitas (total asset turn over and working capital turn over).          The result yield analysis and discussion, then can to understand from ratio liquiditas who theself from Cash Ratio and Current Ratio hipotysis who in propose in to receive. From ratio leverage who theself from Total debt to equity ratio and Total debt to total capital asset hipotysis who in propose in to receive, and Ratio activitas who theself from Total asset turn over and Working capital turn over hipotysis who in propose in to receive.